Impact Of Application Zoning System Edication In The Process Admitting New Students In Makassar City - Hardiman Hardiman; Erman Syarif; Ibrahim Abbas; Alief Saputro (Universitas Negeri Makassar, 2020)
This study aims to determine the impact of the implementation of the zoning system on the admission of new students in the city of Makassar, as well as to determine the government's efforts to overcome the impacts that occur due to the application of the zoning system. This research is included in descriptive qualitative with the subject of public schools in the city of Makassar. Data collection techniques were carried out by observation, interviews, literature review and documentation. The results of this study indicate that the application of the zoning system provides equal opportunities for prospective students, time effectiveness and affordable accommodation costs for students and views all schools with the same quality. The application of zoning benefits to prospective students close to public schools is different for prospective students who are far from schools, lack of facilities causes the application to be less effective, and achievement is no longer a major consideration for prospective students, government efforts in implementing zoning systems such as providing recommendations for prospective students who are far from the school to register at another school close by, try to reduce the zoning quota that is too high for prospective students close to the school, distribute facilities for the continuity of the zoning system well in the future.